Особливості будови автономних безперебійних джерел живлення по типу ecoflow - Гарькавенко, П. О. (ХНУРЕ, 2024)
This paper describes the construction of an autonomous uninterrupted power supply with pulse voltage conversion to improve efficiency. A fundamental block diagram for constructing the autonomous uninterrupted power supply is obtained through the utilization of modern component base. It is demonstrated that employing a few voltage converters at the input and output expands the ways of interaction with the uninterrupted power supply source.
Keywords: безперебійне джерело живлення; розрядка акумуляторів